MEDIA DALAM TANTANGAN INDUSTRI 4.0: ANALISIS PENERAPAN SISTEM DIGITALISASI PADA PERUSAHAAN MEDIA TEMPO - Putri Maulina (SOURCE : Jurnal Ilmu Komunikasi, 2019)
The development of communication and information technology globally has also influenced the management system of print media companies in Indonesia. The print media platform is currently challenged to be able to improve to be able to maintain its existence amidst technological advancements. Tempo is one of the large print media platforms that until now is still popular with Indonesian audiences and is able to survive. This study aims to examine how Tempo implemented a digitalization system in the process of production and media management. The results of the study describe the Tempo digitalisation process emphasized on several sides: (1) optimizing the media convergence system, by integrating media management systems on print media, internet, e-paper and Tempo TV platforms; and (2) differences in content management on print and online media platforms. The digitalization of the Tempo company as a whole has an impact on the management of media companies, both in terms of human resources and media content produced.